MOF‐on‐MOF‐Derived Hollow Co3O4/In2O3 Nanostructure for Efficient Photocatalytic CO2 Reduction - Han, Cheng; Zhang, Xiaodeng; Huang, Shengsheng; Hu, Yue; Yang, Zhi; Li, Ting‐Ting; Li, Qipeng; Qian, Jinjie (Advanced science, 2023)
The photocatalytic transformation of carbon dioxide (CO2) into carbon‐based fuels or chemicals using sustainable solar energy is considered an ideal strategy for simultaneously alleviating the energy shortage and environmental crises. However, owing to the low energy utilization of sunlight and inferior catalytic activity, the conversion efficiency of CO2 photoreduction is far from satisfactory. In this study, a MOF‐derived hollow bimetallic oxide nanomaterial is prepared for the efficient photoreduction of CO2. First, a unique ZIF‐67‐on‐InOF‐1 heterostructure is successfully obtained by growing a secondary Co‐based ZIF‐67 onto the initial InOF‐1 nanorods. The corresponding hollow counterpart has a larger specific surface area after acid etching, and the oxidized bimetallic H‐Co3O4/In2O3 material exhibits abundant heterogeneous interfaces that expose more active sites. The energy band structure of H‐Co3O4/In2O3 corresponds well with the photosensitizer of [Ru(bpy)3]Cl2, which results in a high CO yield of 4828 ± 570 µmol h−1 g−1 and stable activity over a consecutive of six runs, demonstrating adequate photocatalytic performance. This study demonstrates that the rational design of MOF‐on‐MOF heterostructures can completely exploit the synergistic effects between different components, which may be extended to other MOF‐derived nanomaterials as promising catalysts for practical energy conversion and storage. In this article, the hollow counterpart of H‐ZIF‐67‐on‐InOF‐1 presents a larger specific surface area after being acid‐etched, and its corresponding bimetallic oxide of H‐Co3O4/In2O3 owns abundant heterogeneous interfaces, which show a satisfactory photocatalytic CO2 reduction.